Stroke technique changes and expertise level during an all-out time trial in front crawl swimming - Potdevin, F.; Sidney, M.; Pelayo, P.; Alberty, M. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The aim of this study is to compare technical parameters changes in relation to technical skills during an all-out time trial. Eight national level swimmers (GE) and ten occasional swimmers (GNE) performed an all-out time trial of 2 minutes in front crawl stroke. Changes in Speed (dS, m/s), Stroke Length (dSL, m/cycle), Stroke Rate (dSR, hertz), Horizontality of the body (dH, degrees) and Breathing time (dB, s) were calculated between the first and last 30 seconds of the time trial and were compared between groups. Results showed significant greater value in dS, dSL, dH, and dB for GNE, dS and dH being the largest. It is worth noting that the change in SR was not significantly different between groups. dH is significantly correlated to dS and dSL. Such results suggest that keeping the horizontality of the body during an exhaustive exercise is an ability that has priority to be learned in less expert swimmers to improve performance. Consideration of such parameters in the technical analysis could guide skill training process for young swimmers learners.